If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 3x = -6 + 13x Solving -2 + 3x = -6 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -2 + 3x + -13x = -6 + 13x + -13x Combine like terms: 3x + -13x = -10x -2 + -10x = -6 + 13x + -13x Combine like terms: 13x + -13x = 0 -2 + -10x = -6 + 0 -2 + -10x = -6 Add '2' to each side of the equation. -2 + 2 + -10x = -6 + 2 Combine like terms: -2 + 2 = 0 0 + -10x = -6 + 2 -10x = -6 + 2 Combine like terms: -6 + 2 = -4 -10x = -4 Divide each side by '-10'. x = 0.4 Simplifying x = 0.4
| 7n=7.9 | | 4d+6e-5d+4e= | | 24x+30x= | | 5x+6=5x-11 | | 1=5x+1 | | 4m-15=17 | | 6n+58=106 | | 44-2x=14-8x | | 174=4x+3(6x-8) | | s^2+3v-40= | | x^4-12x^3+216x-324=0 | | 3x+8=-27-2x | | g-500=225+g | | 2x+3x+4x-5=22+3+4x | | 2(2)-y=6 | | 7+4x=10+x | | 7n+18=6n+(n-9) | | x+3/4=4 | | 117=4(x+45)+3x | | 1.02g-5=0.61 | | 21y=31.64 | | x+3/4=3/4+x+4 | | 13=7+3s | | 2a^2+11a-63= | | 4+5r=-11 | | 2x/3-3x/5=2 | | 6x-4=2+4x | | x+3+2x+4=x+3+x+6 | | 5-7x/6=3/2 | | 3(x-6)=2(x+7) | | -f(6)=45+10x | | 6x-12=8x+5 |